Handball injuries: Epidemiology and injury characterization: Part 1 - Laver, L.; Luig, P.; Achenbach, L.; Myklebust, G.; Karlsson, J. (Handball Sports Medicine, 2018)
Handball (also referred to as "team handball") is an Olympic team ball sport of worldwide popularity. The sport has continuously developed during recent years, with major evolutions in players` speed, strength, and technique, and as a consequence adaptive changes in tactics and rules of the game. Handball is characterized by intense body contact, frequent intermittent running, pace changes, one-on-one confrontations, and quick direction changes in combination with challenging technique and coordination elements like catching, throwing, passing, and dribbling.